A STUDY OF IVORY AND BONE PLAQUES FROM ZIWIYE IN THE SANANDAJ MUSEUM. (December 2019) - Amelirad, Sheler
Abstract : This article introduces a small group of ivories held in the Sanandaj Museum, which were discovered in 1997 during the seventh season of Nasratolah Motamedi's excavations at Ziwiye, northwest Iran. An investigation of the decorative, figurative, and stylistic characteristics of these pieces reveals a strong Neo-Assyrian influence, with close similarities to the palace reliefs of Ashurnasirpal II at Nimrud, as well as the influence of Assyrianizing Urartian art. These extensive cultural influences on Mannaean art can be seen in terms of political and economic relations with the two regions.